Cuproptosis: potential new direction in diabetes research and treatment - Qu, Jiashu; Wang, Yifan; Wang, Qiuyue (Frontiers in Endocrinology, 2024)
Cuproptosis, a recently discovered form of cell death, stems from an overabundance of copper ions infiltrating mitochondria. These ions directly engage lipoylated proteins, prompting their oligomerization and subsequent loss of iron-sulfur clusters. This sequence induces proteotoxic stress, ultimately culminating in cell death.Type 2 diabetes, a chronic metabolic disorder resulting from a complex interplay of genetic and environmental factors, has not yet been fully understood in terms of its etiology and pathogenesis. Intricately, it is linked to various modalities of cell death, including mitochondrial autophagy, apoptosis, pyroptosis, and ferroptosis. Studies have discovered impaired copper metabolism in individuals with Type 2 diabetes, hinting at a unique role for copper homeostasis in the progression of the disease. To this end, the present research aims to delineate the potential correlation between cuproptosis and Type 2 diabetes by exhaustively reviewing the existing literature. By synthesizing relevant research on cuproptosis, the paper intends to lay the groundwork for a thorough exploration of the pathogenesis of Type 2 diabetes and the development of targeted therapeutic interventions. The ultimate objective is to facilitate a deeper understanding of Type 2 diabetes and to identify novel therapeutic strategies associated with cuproptosis.